2002
DOI: 10.1136/gut.50.6.752
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow derivation of pericryptal myofibroblasts in the mouse and human small intestine and colon

Abstract: Background and aims: In order to establish whether extraintestinal cells contribute to the turnover and repair of gastrointestinal tissues, we studied the colons and small intestines of female mice that had received a male bone marrow transplant, together with gastrointestinal biopsies from female patients that had developed graft versus host disease after receiving a bone marrow transplant from male donors. Methods: Using in situ hybridisation to detect Y chromosomes and immunohistochemistry, we demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
186
4
5

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(202 citation statements)
references
References 31 publications
7
186
4
5
Order By: Relevance
“…Although studies have focused on well-defined immune cell types, recently it has been recognized that chronic inflammation - in addition to inducing the loss of parietal cells and chief cells in the glandular gastric mucosa - stimulates the recruitment of progenitor cell populations to the stomach and their subsequent engraftment. Numerous reports have demonstrated that chronic inflammation leads to the recruitment of bone marrow-derived endothelial progenitors and bone marrow-derived myofibroblasts in mouse models of colitis and hepatitis (82)(83)(84). Similar cell populations are recruited to the stomach in Helicobacter-induced gastritis (T.C.…”
Section: Chronic Inflammation and The Recruitment Of Bone Marrow-derimentioning
confidence: 93%
“…Although studies have focused on well-defined immune cell types, recently it has been recognized that chronic inflammation - in addition to inducing the loss of parietal cells and chief cells in the glandular gastric mucosa - stimulates the recruitment of progenitor cell populations to the stomach and their subsequent engraftment. Numerous reports have demonstrated that chronic inflammation leads to the recruitment of bone marrow-derived endothelial progenitors and bone marrow-derived myofibroblasts in mouse models of colitis and hepatitis (82)(83)(84). Similar cell populations are recruited to the stomach in Helicobacter-induced gastritis (T.C.…”
Section: Chronic Inflammation and The Recruitment Of Bone Marrow-derimentioning
confidence: 93%
“…For reprints contact: Reprints@AlphaMedPress.com 700 Bone Marrow-Derived Fibroblasts Recruited into Fibrotic Lesions transplantation of bone marrow (BM), hematopoietic stem cells or nonhematopoietic mesenchymal stem cells, muscle [7][8][9][10][11], heart [12][13][14], liver [15][16][17][18][19], vascular cells [20,21], and other mesenchymal cells [22][23][24] of donor origin have been detected. Investigators revealed that BM-derived cells can be progenitors for tissue fibroblasts that are recruited through the circulation to populate peripheral organs [25][26][27][28][29]. During renal fibrosis, a small number of fibroblasts were BM origin using BM chimera and transgenic reporter mice [25].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that cancer-induced stroma generated by the human pancreatic cancer cell line consist of BM-derived fibroblasts and that BM-derived fibroblasts become a major component of cancer-induced stromal cells in the later stage of tumor development [26]. Furthermore, BM-derived fibroblasts were engrafted into multiple organs, and it was found that these cells are recruited into injured tissue [27,28]. However, the phenotype and functional roles of BM-derived fibroblasts have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous alkaline phosphatase (AP) was blocked with 20% acetic acid in 150 ml methanol for 3 min at room temperature (Brittan et al, 2002). After one further wash in lectin buffer, the sections were incubated for 30 min at room temperature with rabbit normal serum (no.…”
Section: Selectin Immunoglobulin Fusion Protein Histochemistrymentioning
confidence: 99%